Using 3D approach in learning self-defense for women / Waznati Adenan - Adenan, Waznati (2004)
Learning self-defense is a difficult task especially for women. There are various types of alternatives that can be chosen in order to learn self-defense, such as attending classes, hire a personal tutor, reading books and many more. But for working people, they may not have much time to go to the class regularly. Moreover it is costly and also time consuming. According to this research, the prototype will be develop by using 3D approach and will be focus on the basic technique of self-defense for women. This prototype will be implemented in CD ROM. Three-dimension (3D) can be a part of a multimedia application. Research has shown that learning process become more interesting and effective by using 3D approach, such that students find the aesthetic qualities of the environment motivating, but usability still poses problems. [Jason Elliott, Amy Bruckman, 2002]. 3D concept provides the ability to present object from many angles. The object often looks more realistic. But for learning self-defense using 3D concept without 'user control' is still not enough, because there is no user participation in the learning process. The aim of this research is to focus on the capability of the user-control especially for the multimedia effects on learning. Methodologies used in this project are included conceptualization, data collection, storyboard, modeling, animation and 3D Lingo. This project uses multimediaauthoring tools that needed to build the interaction multimedia application. This approach will enable us to visualize from the first phase until the system is completely developed. 3D approach provides convenience to user to have the interactivity and user-control with the application. User can rotate the figure for any degree that they want to get a clear view of the poses. But, for this project user-control element is not in the real-time application.